Religiosity, Consumer Animosity, and Purchase Unwillingness: The Mediating Role of Product Judgment in a Religiously Motivated Boycott Context - Muhammad Nafil Fikri; Nur Afifah; Wenny Pebrianti; Ahmadi (Journal of Educational Management Research, 2026)
This study aims to examine the effects of religiosity and consumer animosity on purchase unwillingness within a boycott context, with product judgment serving as a mediating variable. A quantitative approach was employed using a survey of 200 Muslim consumers aged 17 years and above who were aware of the boycott issue and expressed concern over related humanitarian matters. The data were analyzed using partial least squares structural equation modeling (PLS-SEM). The findings reveal that religiosity and consumer animosity negatively and significantly influence product judgment, while both variables positively and significantly affect purchase unwillingness. Product judgment also exerts a negative and significant effect on purchase unwillingness and functions as a partial mediator in the relationships between religiosity, consumer animosity, and purchase unwillingness. These results imply that cognitive evaluations of products serve as an important mechanism through which moral commitment and hostile sentiments are translated into refusal to purchase, highlighting the need for firms to address not only emotional reactions but also consumers’ evaluative perceptions in managing boycott situations.